Post-sozialistische Transformation der Einzelhandels Strukturen in Leipzig - Jürgens, Ulrich (ERDKUNDE, 1994)
Within the few years since the opening of the borders of the German Democratic Republic and the subsequent unification of Germany, the influence of a market economy has completely changed the economic and social basis of East German cities and their inhabitants. As a consequence, the systems of wholesale and retail trade that were customary in the East German command economy have also changed. Leipzig will serve as our case study for an analysis of the retail trade structure. We will look at how the system for providing the population with groceries and services has been transformed in the post-socialist era and at the new problems resulting for the city. We will compare the commercial structure of the inner city in 1974,1980 and 1994 respectively. The article analyses how the new developments have affected the manner in which the inhabitants satisfy their needs and what kind of reciprocity there is between the vitality of the inner city and the new shopping malls cropping up in the countryside, a thing that was unknown in East Germany.